Determinants of domestic terrorism: an examination of ethnicpolarization and economic development - Danzell, Orlandrew E. (Terrorism and political violence, 2019)
Many scholars have sought to explain why countries with ethnically heterogeneous populations experience higher levels of political violence, but these studies have produced mixed findings. Unlike most studies that use ethno-linguistic fractionalization indices to examine this relationship, we argue that ethnic polarization is a more appropriate measure to assess the role of ethnicity as a causal factor of domestic terrorism. This paper hypothesizes that high ethnic polarization influences the incidence of domestic terrorism, particularly when intervening economic factors are present. To test three hypotheses, we use negative binomial regression to model data from the Global Terrorism Dataset, World Bank, and the Reynal-Querol (RQ) ethnic polarization index of 116 countries between 1970 and 2012. Our findings show that terrorism is more likely to emerge in societies with high ethnic polarization and economic malaise.